2012
DOI: 10.1111/j.1439-0396.2012.01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects of S‐adenosylmethionine and silybin on canine hepatocytes in vitro

Abstract: Inflammation and oxidative stress are associated with liver injury and development of liver disease. The transcription factors nuclear factor-kappa beta (NF-κB) and nuclear factor erythroid 2-related factor 2 (Nrf2) play critical roles in modulating liver injury and damage. Activation of NF-κB induces production of pro-inflammatory molecules including prostaglandin E2 (PGE2 ), interleukin-8 (IL-8) and macrophage chemotactic protein-1 (MCP-1). Nrf2 regulates genes controlling antioxidants. Our laboratory previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 45 publications
(68 reference statements)
3
35
0
2
Order By: Relevance
“…Hepatorenal injury was characterized by increasing serum ALT, ALP, BUN, and Cr levels after LPS administration (Table 3). Our observations expanded the findings of the previous study, which was performed in vitro on canine hepatocytes (18), by demonstrating the protection of both liver and renal injuries in response to LPS in in vivo conditions. A possible mechanism is that SAMe and silybin in combination could inhibit the inflammation and oxidative stress that are associated with liver injury and development of liver diseases (18).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Hepatorenal injury was characterized by increasing serum ALT, ALP, BUN, and Cr levels after LPS administration (Table 3). Our observations expanded the findings of the previous study, which was performed in vitro on canine hepatocytes (18), by demonstrating the protection of both liver and renal injuries in response to LPS in in vivo conditions. A possible mechanism is that SAMe and silybin in combination could inhibit the inflammation and oxidative stress that are associated with liver injury and development of liver diseases (18).…”
Section: Discussionsupporting
confidence: 75%
“…Our observations expanded the findings of the previous study, which was performed in vitro on canine hepatocytes (18), by demonstrating the protection of both liver and renal injuries in response to LPS in in vivo conditions. A possible mechanism is that SAMe and silybin in combination could inhibit the inflammation and oxidative stress that are associated with liver injury and development of liver diseases (18). Our previous studies showed that oxidative stress inhibition by choline treatment resulted in decreased sepsis severity and good prognosis in dogs with endotoxemia (27).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations